Best multiplier Approximation in L_(p,∅_n ) (B) - Saheb K. Al-Saidy; Naseif J. AL-Jawari; Ali Hussein Zaboon (Al-Mustansiriyah Journal of Science)
The purpose of this paper is to find best multiplier approximation of unbounded functions in L_(p,∅_n ) –space by using Trigonometric polynomials and by de la Vallee- Poussin operators. Also we will estimate the degree of the best multiplier approximation by Weighted –Ditzian-Totik modulus